Cardiac and Liver Fibrosis Assessed by Multiparametric MRI in Patients with Fontan Circulation - Innocenzi, Adriana (2025)
This work was supported by D’Or Institute for Research and Education (IDOR) and FAPERJ (# E-26/010.002144/2019; #E-26/010.001806/2019).